Perspectives on materiality in ancient Egypt : agency, cultural reproduction and change - Érika, Maynart; Velloza, Carolina; Lemos, Rennan (Archaeopress Publishing Ltd, 2018)
Growing out of a colloquium organised in Sao Paulo in March 2016, here nine papers approach the potential of materiality in Ancient Egypt based on several case studies covering a wide range of topics such as Egyptian art, recent perspectives on sex and gender, hierarchies, and the materiality of textual sources and images.